Effect of Pt-Cs2.5H0.5PW12O40 catalyst addition on durability of self-humidifying nanocomposite membranes based on sulfonated poly (ether ether ketone) for proton exchange membrane fuel cell applications. (5th January 2015) - Rowshanzamir, Soosan; Peighambardoust, Seyed Jamaleddin; Parnian, Mohammad Javad; Amirkhanlou, Gholam Reza; Rahnavard, Aylin
Abstract: In this work, the self-humidifying nanocomposite membranes based on SPEEK and Pt supported Cs2.5 H0.5 PW12 O40 catalyst (Pt-Cs2.5 H0.5 PW12 O40 catalyst or Pt-Cs2.5 ) were fabricated and the effect of Pt-Cs2.5 addition on the durability of nanocomposite membranes was investigated. The nanocomposite membranes were prepared by blending different amount (10, 15 and 20%) of catalyst with SPEEK (sulfonation degree is 65.12%) in dimethylacetamide (DMAc). The thermogravimetric analysis (TGA), Fenton's test and open circuit voltage (OCV) measurements were used for evaluation of the thermal, chemical and oxidative stability of these membranes. TGA results indicated that the addition of Pt-Cs2.5 catalysts caused thermal stability improvement. OCV decay rate and residual weight of nanocomposite membrane were used to quantify the membrane degradation rate. The OCV measurements showed 24% decrement in voltage for pure SPEEK and 8% decrement for nanocomposite membrane with 15 wt.% catalyst. The residual weight of nanocomposite membrane with 15 wt.% catalyst increased to over 40 percentage after the Fenton's test. Furthermore, the addition of Pt-Cs2.5 nanoparticles improved the oxidative durability of nanocomposite membranes. Graphical abstract: Highlights: Thermal stability improvement of nanocomposite membranes compared to SPEEK. Mechanical stability improvement of nanocomposite membranes compared to SPEEK. Chemical stability improvement of 15 wt.% nanocomposite membranes compared to SPEEK. Oxidative durability improvement of nanocomposite membranes by addition of Pt-Cs2.5 .